'If I forget anything at all, it's unlikely the stars will accept us … ': sci-fi fan communities, post-Soviet nostalgia and contemporary cinematic experience. (2nd January 2021) - Stepanov, Boris
ABSTRACT: Reception studies is an important trend in contemporary film studies, especially in the current situation, which is characterised by media convergence and audience differentiation. One area of such research, which has not yet developed concerning Soviet and post-Soviet cinema, is the study of fandom. In this paper, I explore post-Soviet fan communities, which play a significant role in the re-appropriation of Soviet sci-fi films and the establishment of a cult aura around science-fiction films. The article seeks not only to outline the emergence of these communities in the 1990–2000s, but also to show their contribution to the formation of a post-Soviet cinematic culture. Moreover, I show how the experience of these communities sheds light on the nature of post-Soviet nostalgia as one of the key impulses of cinematic consumption in post-Soviet culture.